Determining Maritime Health Online Training Needs for Seafarers and Doctors in Maritime Transportation - Seher Suendam Arıcı; Esma Uflaz; Emre Akyüz; Özcan Arslan (Journal of Transportation and Logistics)
After the liberalization of the air transportation sector in 2003, we investigate the factors affecting the preference of air transportation as a mode of transportation and the changes in the air transportation preferences of the Turkish households over the years. For this purpose, we analyze the micro datasets of the household budget surveys using logistic regression and decision tree methods. We find that the most critical factors affecting the air transportation preference of the households for the 2003-2017 period are the income level and the occupation of the household head. The fuel expenditures and the existence of transportation subsidies reduce the air transportation preference of the households. In addition, since 2003, there has been a significant increase in the rate of households preferring air transportation in Turkey. So much so that air transportation is the only mode of transportation that has risen over time. A remarkable finding is that air expenditure of the low-income group is not observed in the 2003 survey, whereas it was a small amount in 2017. The literature on transportation preferences is generally based on primary survey data. This study contributes to the literature as it is applied to a relatively large sample of household micro datasets.